The Practice of Innovating Research Methods. (April 2022) - Lê, Jane Kirsten; Schmid, Torsten
In this article, we examine how scholars innovate research methods. Based on a review of published qualitative strategy and management research, we identify highly innovative academic papers, that is, papers that demonstrate substantial novelty in every part of the research process. We work through these papers in detail to demonstrate their novelty, highlighting concrete ways in which scholars have innovated three interconnected parts of the research process: data generation, data analysis, and presentation of findings. Based on our analysis, we develop a two-layered "iceberg" model of method innovation, which shows that important principles guide the innovative use of organizational research tools. These principles are engaging in holistic innovation, being excruciatingly clear in the presentation of methods, developing theory and method together, and being reflexive in innovating methods. Our model demystifies the largely implicit process of innovating research methods. We hope it serves to orient and encourage a more creative use of methods in future studies.